Timoma do mediastino médio: relato de caso Middle mediastinal thymoma: case report - Elias Kallás (Brazilian Journal of Cardiovascular Surgery, 2005)
Paciente do sexo feminino, 55 anos, branca, com sinais clínicos sugestivos de miastenia gravis há aproximadamente 3 meses. A prova terapêutica com neostigmina evidenciou melhora da disfagia e ptose palpebral. Na radiografia de tórax observou-se imagem ocupando o mediastino médio com projeção à direita. A tomografia computadorizada de tórax revelou a presença de massa no mediastino médio, sendo indicado o tratamento cirúrgico. Chamou nossa atenção a localização pouco usual, já que, preferencialmente, os timomas localizam-se no mediastino superior e anterior. A evolução pós-operatória foi boa, sem complicações. We report on a case of a 55-year-old female, patient, who presented with clinical signs suggestive of myasthenia gravis over a period of approximately 3 months. The therapeutic option using neostigmine gave an improvement of the dysphagia and palpebral ptosis. A chest radiograph image demonstrated a mass occupying the medium mediastinum with projection to the right. Computed tomography of the thorax revealed the presence of a mass in the medium mediastinum, and thus surgery was inicated. During the operation the was was observed in the medium mediastinum suggesting thymoma. What caught our attention was the unusual location of the tumor as normally thymomas are found in the upper and anterior mediastinum.